The main research directions of the foot structure and function and their evolution – literature review - Puszczałowska-Lizis, Ewa (European Journal of Clinical and Experimental Medicine, 2011)
<div class="field-name-field-autorzy-" style="box-sizing: border-box; font-size: 14px; color: #010101; display: inline-block !important; float: left !important; padding: 10px 24px 0px 0px !important; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> In this work have been presented the history of feet research. Their problems also consider the efficiency of the foot in static and dynamic conditions, frequency of deviations below the norm, variability in structure in different periods of ontogeny and difference of sexual dimorphism in selected features of its structure. Part of the study is an attempt to standardize criteria of the evaluation of feet and the way of the results interpretation. Others are focused on searching optimal solutions for manufacture of footwear which prevent deformations and promote development of feet in different ages and also analysis of selected morphofunctional characteristics of feet and morphological characteristics of the body and feet arches. The review of scientific publications showed that over the decades research concepts have been changing, evolving from a relatively simple diagnostic methods to more and more complex and objective in order to obtain accurate results burdened with the lowest risk of measurement errors.